L’antigermanisme et la campagne française pour l’élection du Parlement européen - Ménudier, Henri (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
Anti-German sentiment in France has deep roots that extend back to the middle of the 19th century. A permanent theme of French foreign policy, it manifested itself with force during the campaign for the European elections of June 10, 1979. This explosion can be explained in terms of the fear of a part of the political forces to see themselves dragged too far into a process of European integration that would contribute to submitting France to the economic forces of a Germany very dependent on the United States. The Communists were the main standard bearers of this campaign in which the Gaullists and other politicians participated. An examinationt of the themes of their public statements shows that references to the Third Reich, to trials of former Nazis and to the role that present leaders of the FRG played under Hitler predominated. Criticism of German domestic politics was primarily concerned with the threat to freedoms in the FRG and with the rise of politicians such as Franz Josef Strauss. Comparisons of the economic, commercial and industriel statistics of the Federal Republic of Germany and France fed concerns that prompted once again speculation with respect to German reunification and the association of nuclear weapons with the FRG. In attacking social-democracy the FCP attempted to further undercut Franco-German relations and to accentuate its split with the French Socialist Party. The anti-German campaign did not, in fact, have a great impact on public opinion or government policy. Nevertheless, both the range and persistence of these themes show that xenophobia in general and anti-German sentiment in particular are not on the point of disappearing in France.